"Apostates from Realism: Harold and Margaret Sprout, Princeton, and Geopolitics: 1931–1965". Issue 1 (30th March 2023) - Specter, Matthew
Abstract: By focusing on the joint scholarly work of Harold and Margaret Sprout in the first two-thirds of their academic career, this article aims to recover the work of an important female international thinker from relative obscurity. The Sprouts were important protagonists in the making of a geopolitical strand of realism centered at Princeton University during the war. Historians of realism focused on developments in the mid-1950s centered on Columbia and Chicago have neglected the circle around Edward March Earle at Princeton which gave the Sprouts their start. In Section I, I use a close reading of archives at Princeton, as well as an unpublished autobiography that the couple wrote before Harold's death in 1980 (amended by Margaret in 1995), to establish the collaborative nature of their scholarship and the challenges Margaret faced as an unsalaried researcher without a formal academic appointment. In Section II, I trace the Sprouts' work from the 1939–1940 work on naval power through to a critical review of Hans Morgenthau in 1949. In Section III, I argue that Man-Milieu Relationship Hypotheses (1956) constituted their break with the geopolitical realism that they had championed through the late 1940s. I also show how their work from 1956 to 1965, critical of teleology and reification of large-scale "influences of geography" and "elements of national power" made them pioneers in cognitive foreign policy analysis (like Snyder, Burton, and Sapin, 1954) and forerunners of constructivism. I conclude with some reflections on their marginalization by international relations theory and history alike.